The anatomy of police legitimacy: Dialogue, power and procedural justice - Martin, Richard (Theoretical criminology, 2021)
In a series of recent influential papers, Anthony Bottoms and Justice Tankebe make the case for a ‘dialogic model’ of police legitimacy, wherein legitimacy is envisaged as emergent in a process through which the police, as power-holders, make claims to authority which are, in turn, responded to by audiences. Our aim in this article is to analyse this model. We argue that while it has the potential to direct legitimacy research along paths hitherto poorly explored, there is a need for conceptual refinement and development in three key respects. First, through recognition of micro- and meso-levels of legitimation. Second, acknowledgement that police claims-making is contingent on the authorization and endorsement of other actors. Third, a fuller consideration of the qualified role of dialogue—i.e. communication between police and policed—in public audiences’ legitimacy assessments. In the spirit of critical engagement and conceptual exploration, this article develops these three insights to propose a modified version of the dialogic model.